The readiness of Big Data implementation in organizations from the aspects of knowledge, skills and user acceptance/ Nur Naja Ismail - Ismail, Nur Naja (Faculty of Information Management, 2021)
This study is conducted to understand the readiness of Big Data implementation in organizational sectors from the aspects of knowledge, skills and user acceptance. Organizations now has been experiencing the challenges of the presence of large amount of data into their databases. Those changes can be seen from the effect of technological matters such as the use of larger memory, advanced computers and new networks being provided. Most of the organizations nowadays have changed and evolved into the advancement of technology. However, in some organizations which has less amount of data being transmitted and still using traditional computer may not be ready to accept the presence of Big Data into their sectors. Many organizations have implemented Big Data yet some are still considering Big Data as a new thing. The quantitative method of research has utilized three factors of measurement which are knowledge, skills and user acceptance towards Big Data in organizations. This measurement analyses on the level of respondents towards the implementation of Big Data whether they are ready enough or still in unidentified status. A structured questionnaire is used to measure the findings of the readiness of Big Data in organizations. The respondents comprise of the employees of public and private sectors of various departments and units. Each element of the questionnaire is being assessed whether the particular organizations are ready enough to accept the implementation of Big Data as well as accepted the challenges occur within. This study will then measure the leading of the organizations either towards Big Data implementation or in the other way round.